1998
DOI: 10.1007/bf02341782
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of carpal tunnel syndrome according to the neurophysiological classification

Abstract: Although many studies on carpal tunnel syndrome (CTS) have been reported, few data on the natural history of CTS are available. Knowledge of the natural course of the disease has significant clinical and therapeutic value. We prospectively followed up 80 cases of untreated CTS. The evaluation was based on self-administered questionnaires and on neurophysiological investigation. According to the neurophysiological classification, cases of CTS were divided into six groups on the basis of impairment severity: neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 12 publications
0
22
0
1
Order By: Relevance
“…The diagnosis of carpal tunnel syndrome is essentially clinical, as electrodiagnostic tests are known to have 13% rates of false-negative results 2 and 18% rates of false-positive results 3 , and objective confirmation of the diagnosis can often be elusive [1][2][3][4][5] . Furthermore, the natural history of carpal tunnel syndrome remains unclear [6][7][8] . Accordingly, questions have been raised as to when and which treatment is most appropriate 9,10 .…”
mentioning
confidence: 99%
“…The diagnosis of carpal tunnel syndrome is essentially clinical, as electrodiagnostic tests are known to have 13% rates of false-negative results 2 and 18% rates of false-positive results 3 , and objective confirmation of the diagnosis can often be elusive [1][2][3][4][5] . Furthermore, the natural history of carpal tunnel syndrome remains unclear [6][7][8] . Accordingly, questions have been raised as to when and which treatment is most appropriate 9,10 .…”
mentioning
confidence: 99%
“…First, this study was retrospective in design and lacked a control group. Ideally, there should have been a control group of patients without treatment, since some patients improve spontaneously (34, 35). Second, our outcome measure where failure of injection is defined as receiving subsequent treatment may not adequately capture clinically relevant failures, where patients have ongoing symptoms of CTS but elect for some other reason not to receive subsequent treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A rational approach to the treatment of extreme CTS should first take into account the natural evolution of the disease. Studies of the natural history of idiopathic CTS have shown that symptoms tend to decrease with time, and a relevant percentage of patients may spontaneously improve 17, 20, 21. Some investigators have hypothesized that the disease may assume a self‐limited course due to a reorganization of functional relationships between the median nerve and the carpal canal 21.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the natural history of idiopathic CTS have shown that symptoms tend to decrease with time, and a relevant percentage of patients may spontaneously improve 17, 20, 21. Some investigators have hypothesized that the disease may assume a self‐limited course due to a reorganization of functional relationships between the median nerve and the carpal canal 21. Unexpectedly, in the large series of untreated patients reported by Padua and co‐workers, about half of 43 hands with severe CTS (absence of median SNAP and prolonged DML) showed spontaneous reappearance of the median SNAP 20.…”
Section: Discussionmentioning
confidence: 99%